The effect of transcranial direct current stimulation on craving in patients with alcohol dependence: A pilot study - N Nageswara Rao; Paradesi Ramya Keerthi; P Ravi Kiran; B Durganjali (Telangana Journal of Psychiatry, 2023)
Background: Craving can play a critical role in the development and maintenance of alcohol dependence, and has been implicated in relapse, and is currently one of the diagnostic criteria for substance use disorders in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. Transcranial direct current stimulation (tDCS) is the application of a weak electrical current (1–2 mA) to the scalp to modulate the activity of neurons in the brain. It is the need of the hour to know about the effect of tDCS on craving in patients with alcohol dependence. Aims and Objectives: The aim of this study was to assess the effect of tDCS on craving in patients with alcohol dependence. Subjects and Methods: Thirty patients who attended the outpatient department at the Department of Psychiatry, S. V. Medical College, Tirupati, and diagnosed with mental and behavioral disorders due to the use of alcohol dependence syndrome according to the International Classification of Diseases, Tenth Revision were selected. These patients were administered a semi-structured pro forma, Alcohol Use Disorders Identification Test, Severity of Alcohol Dependence Questionnaire, Penn Alcohol Craving Scale (PACS), and Alcohol Craving Questionnaire-Short Form-Revised (ACQ-SF-R). Fifteen patients were given six sessions of sham-tDCS at 0.5 mA for 20 min each session, while the other 15 patients were given six sessions of tDCS at 2 mA for 20 min each session. After this, the PACS and ACQ-SF-R scales were readministered. Results: The mean period of abstinence from alcohol among cases was 1.007 ± 1.769y, while among controls was 0.400 ± 0.633y. On applying chi 2 test P value is 0.221, Hence it is insignificant. The mean pack-years among cases was 2.980 ± 6.114, while among controls was 1.270 ± 3.254. The mean alcohol consumption among cases was 6.540 ± 4.047 standard drinks, while that of controls was 7.531 ± 4.889 standard drinks. The mean compulsivity score among cases before tDCS was 5.32 ± 1.699 and after tDCS was 1.19 ± 0.698; the mean compulsivity score among controls before tDCS was 5.13 ± 1.473 and after tDCS was 1.36 ± 0.792. The P value for compulsivity score between cases and controls was >0.05 both before and after tDCS. Conclusion: tDCS was well tolerated with no significant adverse events. Thus, tDCS over the dorsolateral prefrontal cortex is a promising adjunctive clinical tool that could be used to reduce alcohol craving and facilitate alcoholism cessation.